2016
DOI: 10.1016/j.ajo.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Hysteresis and Progressive Retinal Nerve Fiber Layer Loss in Glaucoma

Abstract: Purpose To investigate the relationship between corneal hysteresis (CH) and progressive retinal nerve fiber layer (RNFL) loss in a cohort of patients with glaucoma followed prospectively over time. Design Prospective observational cohort study. Methods One-hundred and eighty-six eyes of 133 patients with glaucoma followed for an average of 3.8 ± 0.8 years, with a median of 9 visits during follow-up. The CH measurements were acquired using the Ocular Response Analyzer (Reichert Instruments, Depew, NY) and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…[41][42][43][44][45] The association between CH and LCCI provides a plausible explanation for the association of CH with glaucoma progression. [41][42][43][44][45] In eyes with smaller hysteresis, pressure would not be dissipated too much. Thus, a higher proportion of IOP-derived energy would be used in elastic changes resulting in greater LC deformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45] The association between CH and LCCI provides a plausible explanation for the association of CH with glaucoma progression. [41][42][43][44][45] In eyes with smaller hysteresis, pressure would not be dissipated too much. Thus, a higher proportion of IOP-derived energy would be used in elastic changes resulting in greater LC deformation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…) and with faster rates of retinal nerve fibre layer (RNFL) loss over time (Zhang et al. ). In childhood glaucoma, lower CH values have been also reported (Luce ; Perucho‐González et al.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted our decision to separately evaluate male and female groups, as well as older and younger, groups. Other studies have already demonstrated that low CH is associated with glaucoma progression 3,4 . Here, we evaluated the relationship between systemic antioxidative status and CH; to the best of our knowledge, this is the first study to do so.…”
Section: Discussionmentioning
confidence: 89%
“…Measurements with a score of at least 6.5 were included. Details of these techniques have been reported previously 4,26 . Statistical Analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation